Ultrasound technology in green chemistry - Sillanpää, Mika (SpringerBriefs in molecular scie, 2011)
As a new and rapidly growing science, the applications of ultrasound methods in environmental technology hold a promising future. Compared to conventional methods, ultrasonication can bring several benefits such as being environmentally friendly (no toxic chemical are used or produced), low cost, and compact, allowing on-site treatment. Besides an overview featuring the background behind ultrasonic technology, this brief summarizes the main studies and innovations reported in recent research that has utilized ultrasound methods in environmental analysis, water, and sludge treatment, soil and sediment remediation to air purification. -Publisher's descripti